Penerapan Metode Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Hasil Belajar Matematika di SMP - Umar Wirantasa (Indo Publishing, 2025)
This community service project aims to improve mathematics learning outcomes and student participation in junior high school (SMP) through the implementation of the Student Teams-Achievement Divisions (STAD) cooperative learning method. The activities included teacher training, classroom facilitation, formation of heterogeneous student teams, group discussions, individual quizzes, and assessment of learning outcomes. Data were collected using pre-tests and post-tests, classroom observation, and teacher and student satisfaction questionnaires. The results show a significant improvement in students’ mathematics achievement, with the average score increasing from 61 to 82 and the mastery percentage rising from 55% to 90%. In addition, students’ active participation in discussions, teamwork, and task completion increased considerably. Teachers reported easier classroom management and better monitoring of student progress, while students felt more motivated and enjoyed learning. This community service demonstrates that the STAD method is effective in enhancing academic performance, learning motivation, and social skills, while also providing practical experience for teachers in applying cooperative learning strategies.